The relationship of taqlīd and fanaticism to the fallacy and truth perception of ijtihād - Asar, Abdul Karim (Universiti Malaysia Pahang, 2021)
This study attempts to shed light on the relationship of taqlīd and fanaticism to the fallacy and truth perception of ijtihād. Looking at the meaning of taqlīd and fanaticism; the researcher finds that there is strong relationship of taqlīd and fanaticism to the two main schools of thought known as “al-takhṭiaћ” [fallacy perception of ijtihād] and “al-taṣwīb” [truth perception of ijtihād]. Both opinions have caused taqlīd and fanaticism to preferred madzhāhib; moreover the “al-takhṭiaћ” school of thought which has negative impact on Islāmic nation, as it necessitates constant conflict between Muslims: common people, as well as among scholars who do not achieve the level of ijtihād. At the end, the researcher has concluded that the more appropriate and correct view is that all mujtahids who have did their best, are correct in their ijtihād; however the truth is only with one of them, not all of them.